2010
DOI: 10.1111/j.1574-6941.2010.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of  flow cytometric sorting to better assess the diversity of small photosynthetic eukaryotes in the English Channel

Abstract: Small photosynthetic eukaryotes are key primary producers in marine waters. In recent years, their diversity has been studied by the analysis of 18S rRNA gene sequences directly amplified and cloned from filtered natural samples. However, these clone libraries are often dominated by nonphotosynthetic organisms and few sequences from autotrophs are recovered. In the present paper, we developed a new approach based on flow cytometry. Photosynthetic pico-, nano- and phycoerythrin-containing (PE-) eukaryotes from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 36 publications
8
103
2
Order By: Relevance
“…Consistent with this effect, all mismatches occurred in GC-rich regions and were predominantly substitution errors. Significantly, haptophytes have been shown to be routinely underrepresented when in the presence of other eukaryotic DNA (76,77), and Marie et al found that haptophytes present in marine samples had higher GC contents along the 18S rRNA gene than the other groups present (e.g., 49.2% for Haptophyta compared to 45.9% for Chlorophyta) (77).…”
Section: Figmentioning
confidence: 99%
“…Consistent with this effect, all mismatches occurred in GC-rich regions and were predominantly substitution errors. Significantly, haptophytes have been shown to be routinely underrepresented when in the presence of other eukaryotic DNA (76,77), and Marie et al found that haptophytes present in marine samples had higher GC contents along the 18S rRNA gene than the other groups present (e.g., 49.2% for Haptophyta compared to 45.9% for Chlorophyta) (77).…”
Section: Figmentioning
confidence: 99%
“…Beside portals dedicated to the annotation of each of the different genomes, web sites focused on comparative analysis between the different organisms belonging to the green lineage, as PLAZA (bioinformatics.psb.ugent.be/plaza/) (Proost et al, 2009) and its derivative Pico-PLAZA (bioinformatics.psb.ugent.be/pico-plaza/) are now available. Such tools for comparative approaches, coupled to the development of new sequencing possibilities for both new genomes and metagenomes (Cheung et al, 2010;Marie et al, 2010) from various environments open the door to a better understanding of the adaptations of the organisms to their environment.…”
Section: B Ecology and Molecular Evolution Of Oceanic Picoplanktonicmentioning
confidence: 99%
“…The 18 S Smallest predators of the oceans J del Campo et al Smallest predators of the oceans J del Campo et al rDNA sequence of our isolate was highly similar to environmental sequences retrieved from the Mediterranean Sea (BL000921.31 and BL010625. 12; Massana et al, 2004), the Sargasso Sea (SSRPE06; Not et al, 2007), and the English Channel (RA070625T.047; Marie et al, 2010). Therefore, we decided to focus in the rhizarian isolate for the rest of our study, given its taxonomic novelty and its similarity with environmental marine sequences.…”
Section: Resultsmentioning
confidence: 99%